ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (Studi Empiris Pada Auditor BPKP Perwakilan Provinsi Jawa Tengah) - Purwoko Setya Nugroho, 12.05.52.0014; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze empirically the effect of independence, integrity, professionalism, competence, objectivity and compliance with the code of conduct on audit quality in auditor BPKP Representative of Central Java province. The population used in this study are all auditor BPKP Representative of Central Java province, amounting to 229. Based on the formula Slovin obtained a sample of 71 auditors. The selected sample is the auditor of public sector who have passed education and training JFA (Functional Auditor). The sampling technique convenience sampling method that is simple sample form is done by selecting a free sample according to the needs of researchers. In this study, the dependent variable used is the quality of the audit. For independent variables consist of independence, integrity, professionalism, competence, objectivity and adherence to a code of ethics. To analyze the hypothesis used multiple linear regression analysis. The results showed that the independence, integrity, professionalism, competence, objectivity and compliance code of conduct positive and significant effect on audit quality.  Keywords:  Independence, Integrity,Profesiomalisme, Competence, Objectivity, Code Compliance, Quality Audit